Representing Islam: old myths in the new medium - Muzayin Nazaruddin (Asian Journal of Media and Communication, 2018)
This study focuses on the adaptation of Islamic-mystic magazines into religious soap operas in Indonesia. This study concludes that for the producers, Islamic soap opera plays an economic function: to get more audiences and more economic profit. But, for the audience, religious soap opera plays a cultural function: to maintain and reconfirm their traditional beliefs. It leads us to the theoretical conclusion that this adaptation practice is a mechanism of self-translation of Javanese culture.